Il Santo Sepolcro di Gerusalemme. Appunti di ricerca storico-architettonica - Garbarino, O. (Liber Annuus, 2005)
Abstract This study considers the numerous written sources regarding the Holy Sepulcher, which supply useful elements to describe a probable conformation of the monument with the distribution of the main liturgical spaces that allow to date some of the most important restructurings that happened in the course of the centuries. In recent times, moreover, archaeological surveys and diggings have allowed, to identify the sequence and the material consistency of the several architectonic transformations. It was the reordering, the comparison, and the filological verification of all these data, all based on the resetting and the graphic representation of the contextual frameworks that provided the method and the aim of the present research. The critical reading of the previous studies and of the new surveys realized on the spot, have highlighted, in particular, the articulated number of the constructive stages, through which the complex of Constantine has been realized in the IV century. Therefore, the uninterrupted series of restorations have become evident along with the restructurings characteristic of the period between the destructions perpetrated by the Persians in 612 and the inauguration of the crusaderʼs work after the conquest of Jerusalem in 1099.